Zakat Produktif Dalam Upaya Mengentaskan Kemiskinan (Studi Kasus: Baznas DKI Jakarta) - Achmad Diponegoro; Abdullah Ahmad; Meylan Cahya Ningrum (Lembaga Pengembangan Kinerja Dosen, 2024)
Islam as a religion of rahmatan lil alamin, its teachings not only contain ritual worship, but also social worship. Zakat is a form of worship which is an obligation that must be fulfilled by every Muslim who has excess wealth. The potential figure for zakat in Indonesia is 327 trillion per year. The large potential zakat figures are not balanced with the welfare of the people, especially Muslims because the poverty rate in Indonesia is still high. The distribution of zakat in Indonesia is considered to be ineffective in overcoming the problem of poverty. BAZNAS as a national zakat management institution is now following in the footsteps of implementing productive zakat, although there are not many, but in Jakarta there are already BAZNAS that accept productive zakat, one of which is BAZNAS DKI Jakarta. This research was conducted to see the efforts and strategies of BAZNAS DKI Jakarta in managing productive zakat to reduce poverty. This research uses a qualitative descriptive method with case study techniques. Data was obtained from interviews with BAZNAS sources as primary informants and the community as secondary informants. The results of the research show that the role of productive zakat in alleviating poverty is just helping the mustahik in running a selling business and has not provided any significant changes to the mustahik, and BAZNAS DKI Jakarta has three strategies in managing productive zakat, namely direct assistance (cash), indirect assistance. directly (products), and empowerment of disabled people.